Hydrochlorothiazide‐induced photosensitivity in a psoriasis patient following exposure to narrow‐band ultraviolet B excimer therapy. Issue 5 (6th June 2019) - Rosenthal, Amanda; Herrmann, Jennifer
Abstract: Drug‐induced photosensitivity develops when the use of oral or topical photosensitizing medications creates a rash after exposure to ultraviolet (UV) radiation. Medications most commonly implicated in photosensitive drug reactions include amiodarone, nonsteroidal anti‐inflammatories, thiazides, tetracycline antibiotics, chlorpromazine, and fluoroquinolones. It is generally believed that drug‐induced photosensitivity is an UVA phenomenon, caused by UV wavelengths between 315 and 400 nm. Here, we present a case of hydrochlorothiazide (HCTZ)‐induced photosensitivity following exposure to 308‐nm narrow‐band (nb) UVB light emitted from an excimer laser in a patient undergoing treatment for plaque psoriasis. This patient had received biweekly treatments with the excimer laser for years prior without any history of adverse reactions. We believe that our patient suffered an acute photosensitivity to UVB due to new‐onset HCTZ. Because nb UVB–emitting lasers are used to treat many dermatologic conditions, physicians should be aware of potential photosensitivity reactions, review medication lists and counsel patients accordingly.